Akkermansia muciniphila-directed polyphenol chlorogenic acid intervention for obesity in mice - Xiaoxiang Gao; Chenbo Yue; Ruocen Tian; Leilei Yu; Fengwei Tian; Jianxin Zhao; Wei Chen; Qixiao Zhai (Food Science and Human Wellness)
Akkermansia muciniphila play an important in ameliorating obesity but is not allowed for direct consumption in most countries. To date, microbiota-directed foods selectively promote the targeted human gut microbes, providing a strategy for A. muciniphila enhancement. Multiple studies have indicated the potential regulation of the polyphenol on A. muciniphila. Therefore, a polyphenol screening based on A. muciniphila upregulation was performed in mice. Chlorogenic acid (CGA) exhibited a greater response to A. muciniphila upregulation. Furthermore, we found that CGA did not directly promote A. muciniphila growth or mucin secretion. Microbiome and metabolomics revealed that the increased abundance of A. muciniphila resulted from the inhibition of CGA on Desulfovibrio and Alistipes and the influence of docosahexaenoic acid, β-hydroxybutyrate, and N-acetyl-lactosamine. Finally, to confirm the regulation of CGA on A. muciniphila under disease conditions, high-fat diet-fed mice were established. The results showed CGA promoted A. muciniphila growth, and we expectedly found that CGA suppressed the augment in body weight of mice, significantly attenuated adipose tissue abnormality, provided liver protection and improved gut barrier integrity. These results suggest that CGA inhibits the development of obesity. Overall, our results indicate that microbiota-directed food is a promising approach for the treatment of obesity.